Thermal requirements for the development of the nematogenic fungi Paecilomyces lilacinus - Fioretto, Ada Marina Cagliari; Villacorta, Amador (Pesquisa Agropecuaria Brasileira, 2014)
The fungus Paecilomyces lilacinus (Thom.) Samson was inoculated and cultured on potato dextrose agar medium at eleven different temperature levels, ranging from 5°C to 35°C for eight days. The technique used to evaluate the growth performance of the fungus colony on the surface medium was the radial surface growth. The temperatures 5°C and 35°C proved to be biostatic, and the temperatures of 24°C and 25°C were considered as optimum for maximum fungus growth, since they did not differ significantly (P=0,05). Lower temperature threshold of development, 10,9°C, was estimated by using linear regression; hence lower temperatures were considered to be more suitable for storage of P. lilacinus.